Lightwork Texts on and from Collaborative Multimedia Theatre. - Mermikides, Alex (Playtext series., 2022)
Collection of performance texts from the experimental theatre company Lightwork, along with short essays by key participants. Geared around collaborative creation, it covers an array of approaches including devised, multimedia and site-specific work, providing a rich resource for those making or studying contemporary performance. 20 illus.